Novel sounds, native responses: exploring the acoustic consequences of Eleutherodactylus johnstonei’s invasion in urban areas - Melo, Natalia Bispo Vieira; Both, Camila; Brasileiro, Cinthia A. (Frontiers in Amphibian and Reptile Science, 2024)
Background Biological invasions pose a critical threat to biodiversity, affecting ecological balance and native species’ communication. Eleutherodactylus johnstonei, an exotic anuran in São Paulo, vocalizes at intensities that could interfere with native anuran species, potentially causing acoustic masking. Methods We evaluated the effects of E. johnstonei's calls on the vocalizations of two native species, Scinax imbegue and Physalaemus cuvieri, both with and without spectral overlap with the invasive species. Field playbacks were conducted using six versions of stimuli, including E. johnstonei's calls, the native Boana bischoffi (as a control), and white noise. We recorded response calls and behavioral changes of S. imbegue and P. cuvieri males. Results The calls of E. johnstonei did not affect the spectral or temporal parameters of the native species’ announcement calls. However, S. imbegue males displayed behavioral responses such as cessation of vocalization or movement away from the noise source. Additionally, B. bischoffi's calls and white noise influenced native species’ call parameters. Discussion Our findings reveal that exotic species’ vocalizations may disrupt native anurans’ acoustic behavior. This impact varies with species and context, underlining the need for further research on anuran acoustic interactions across different frequencies and acoustic environments to fully understand the effects of exotic acoustic interference.